Pharmaceutical and experimental-clinical aspects of photodynamic therapy combined with chemotherapy for malignant and premalignant tumors - Yu. S. Romanko; I. V. Reshetov (Сибирский онкологический журнал, 2025)
The aim of the study was to analyze the effectiveness of experimental and clinical photodynamic therapy combined with chemotherapy in the treatment of malignant and premalignant lesions. Material and methods. The WoS, Scopus, MedLine, and RSCI databases have been searched and analyzed on this issue, mainly over the past 7 years. We found 288 sources on pharmaceutical and experimental-clinical studies of combined photodynamic therapy in combination with chemotherapy to compare the therapeutic effects of combination therapy and monotherapy, of which 50 were included in the review. Results. Photodynamic therapy is a new cancer treatment technology that has become increasingly common in recent years. In some cases, it is often an alternative method of treating cancer when there is a high risk of side effects and complications during traditional treatments such as surgery, radiation therapy and chemotherapy. The review summarized current pharmaceutical and experimental-clinical aspects of performing photodynamic therapy combined with chemotherapy. Despite the fact that the combination of photodynamic therapy and chemotherapy gives the best results in the treatment of malignant neoplasms, this treatment strategy has limitations. One of the major challenges is that very little research has been conducted in this field. Additional research is also needed to understand the mechanisms of increasing the effectiveness of combined photodynamic therapy. The challenge of reaching and effectively treating deeper tissues remains a significant obstacle to wider application of photodynamic therapy. Therefore, further research is needed to determine the most effective photosensitizers and technologies for using non-ionizing radiation. In the review, we have also shown new strategies of using nanopharmaceuticals, which demonstrated encouraging results. Conclusion. The improved therapeutic efficacy with reduced side effects of combination of photodynamic therapy and chemotherapy deserve further comprehensive study.